2019
DOI: 10.1007/s40820-019-0285-x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Isolation and Multiplexed Detection of Exosome Tumor Markers Via Queued Beads Combined with Quantum Dots in a Microarray

Abstract: HIGHLIGHTS • A bead-based microarray for exosome isolation and multiplexed tumor marker detection was developed. • The beads are uniformly trapped and queued among the micropillars in the chip, which can avoid optical interference and enable more accurate test results. • The results with different types of lung cancer exosome samples showed distinctive marker expression levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 39 publications
0
33
0
Order By: Relevance
“…72 Bai et al have captured lung cancer EVs through queued beads functionalized with antibodies and combined with quantum dots in a microarray, which showed distinctive lung cancer marker detection level. 73 Immunoaffinity can isolate EV subpopulation, especially for tumor EVs, while limited sample processing volume is a big challenge for the immunoaffinity.…”
Section: Extracellular Vesicle Isolation and Enrichmentmentioning
confidence: 99%
“…72 Bai et al have captured lung cancer EVs through queued beads functionalized with antibodies and combined with quantum dots in a microarray, which showed distinctive lung cancer marker detection level. 73 Immunoaffinity can isolate EV subpopulation, especially for tumor EVs, while limited sample processing volume is a big challenge for the immunoaffinity.…”
Section: Extracellular Vesicle Isolation and Enrichmentmentioning
confidence: 99%
“…Exosomes, as circulating biomarkers (exosomal protein, miRNA, and DNA), have received tremendous attention for non‐invasive diagnosis and prognosis of patients with cancer and other diseases. [ 14,110 ] So far, many detection technologies, such as nanoparticle tracking analysis, enzyme‐linked immunosorbent assay (ELISA) and flow cytometry, have been applied to analyze the number, size, and surface proteins or miRNA content of exosomes. [ 12,113,114 ] However, these detection technologies still face many problems, such as the low levels of exosomal markers and the heterogeneous exosome subpopulation, which limit the sensitivity and selectivity of exosome detection.…”
Section: Microfluidics‐based Exosome Detection Strategiesmentioning
confidence: 99%
“…By applying immune-based capture technique for the CSPG4 epitope, the authors identified a specific protein profile of MTEX that was qualitatively and quantitatively distinct from normal cell-derived exosomes in plasma of patients with melanoma. In a similar way, Bai et al (185) recently developed an immuno-based microfluidic chip using a quantum dot multiplex detection system to characterize lung cancer exosomes for the expression of different cancer-related surface molecules.…”
Section: Extracellular Vesicles As Fingerprint Of Tumor Metabolic Statementioning
confidence: 99%